107k views
2 votes
I need help with this problem. I tried doing it but it seems wrong.Solve by substitution

I need help with this problem. I tried doing it but it seems wrong.Solve by substitution-example-1

1 Answer

6 votes

Let's start fresh.

Solve the first equation for y:


\begin{gathered} 3x-y=-8 \\ 3x+8=y \\ or \\ y=3x+8 \end{gathered}

Now, substitute it into 2nd equation and then solve for x:

5x + 2y = 5

5x + 2(3x + 8) = 5

5x + 6x + 16 = 5

11x = 5 - 16

11x = -11

x = -11/11

x = -1


\begin{gathered} 5x+2y=5 \\ 5x+2(3x+8)=5 \\ 5x+6x+16=5_{}_{} \\ 11x=5-16 \\ 11x=-11 \\ x=-(11)/(11) \\ x=-1 \end{gathered}

We knew,

y = 3x + 8

We plug the value of x and get y:

y = 3x + 8

y = 3(-1) + 8

y = -3 + 8

y = 5

Hence, the solution of the system is:

x = - 1

y = 5

User AndyM
by
4.5k points